Effect of fiber orientation on ultimate tensile strength and Young's modulus of fabricated glass fiber reinforced polymer plates - Syamsir A.; Amat A.H.; Usman F.; Itam Z.; Kamal N.L.M.; Zahari N.M.; Chairi M.; Imani R. (American Institute of Physics Inc., 2023)
Fiber Reinforced polymer (FRP) composites remain unconventional material in the civil industry. Generally, composite is material made by fusing two or more different material in ways that produce new material with higher superior properties than the original material. There are several advantageous composites could bring in the material engineer that is high strength to width ratio, inert and corrosion resistance. In this study, hand lay-up method was selected to fabricate the glass fiber reinforced polymer (GFRP) plates with various fibre orientation of 0 o, 30 o, 45 o, and 90o. The plate was fabricated for tensile test and the dimension of the specimen is as per ASTM D3039 M. The test was performed at room temperature with 0.5 mm / min head displacement and loaded with monolithically tension. It was found that plate A has the tensile strength of 446.7 MPa, while plate D has the lowest tensile strength of 198.4 MPa. Plate A also shows the highest Youngs's Modulus (E) of 19.9 GPa while plate D produced the lowest E of 12 GPa. This is due to the most tensile strength contribution is come from fiber with 0o fiber orientation. 2021 American Institute of Physics Inc.. All rights reserved.